‘IUS POSTLIMINII’ JAKO PODSTAWA UZNANIA CIĄGŁOŚCI PRZEDWOJENNYCH I DZISIEJSZYCH PAŃSTW BAŁTYCKICH - Karski, Karol (Zeszyty Prawnicze, 2016)
‘IUS POSTLIMINII’ AS THE GROUNDS FOR THE RECOGNITION OF CONTINUITY BETWEEN THE PRE-WAR AND THE PRESENT-DAY BALTIC STATES Summary Postliminium was applied to describe the status of a Roman citizen who was taken captive during a war and then regained his freedom. If he managed to return from captivity, then the moment he crossed the border of the Roman state, legally his rights and legal relationships were restored (though with some exceptions). This institution has become part of international law and has developed a life of its own. Hardly anyone remembers the Roman origins of many legal constructs, though they are still in force. This is the strength of Roman law. One of the examples of the application of Roman law constructs may be observed in the Baltic States, which were annexed by the USSR in 1940. Due to the change in international law which occurred at the turn of the 1920s and 30s in outcome of the Briand-Kellogg Pact, the acquisition of territory as a result of the use of military force in contravention of its provisions was no longer admissible. In 1991 the Baltic States regained their independence. By proclaiming it, they took the position that they were continuing their inter-war statehood and that all the international agreements they had concluded until 1940 were still valid. The present-day Baltic States are not regarded as legal successors of the USSR. This means that a state conforming to international law has been restored and an end put to an illegal occupation. The example of the Baltic States shows that ius postliminii is a permanent feature of the international legal order. Lithuania, Latvia, and Estonia may have lost their independence for 50 years, but subsequently they returned as states to the international community. They are regarded as identical with those states which were annexed during the Second World War by the USSR. They have been restored and continue to exercise all the rights and obligations they had before 1940.